Key Factors For Successful Flood Disaster Knowledge Transfer In Riverbank Areas: A Literature Review - Rifanti, Dinda Putri; Permatasari, Karina Putri; Siswahyuni, Zulaika (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2024)
Introduction: Floods are seasonal disasters when water capacity overflows from existing waves and drowns the surrounding land. The losses incurred by floods, especially indirect losses, rank first or second after earthquakes or tsunamis. Methods: A systematic search of Cochrane, Google Scholar, PubMed, Scopus, Embase and Web of Science database reviews. The following keywords were used to conduct the literature search: "Flood", "Capacity Building", and "Natural Disaster". Results: From the review of 14 abstracts and titles, six were determined to meet the research objectives. Overall, Interaction and Collaboration in Flood Disaster Knowledge Transfer, Experience, Social Learning, and Transdisciplinary Approach in Flood Disaster Knowledge Transfer, Knowledge Management and Absorption Capacity in Flood Disaster Knowledge Transfer. Conclusion: Interaction and collaboration in flood disaster knowledge transfer is essential to reduce disaster risks and losses. Collaboration between all relevant sectors, such as government, business, community, academia, and mass media, can also help reduce flood risk through disaster programs. Experience, social learning and transdisciplinary approaches all play a role in improving the knowledge capacity and attitudes of communities in dealing with floods. Knowledge management and absorptive capacity in flood disaster knowledge transfer are also important to reduce disaster losses and improve disaster preparedness